Project-Based Recycling Education: A Practical Approach to Environmental Education - Tan, Dingliang (Science Insights Education Frontiers, 2025)
Amid growing resource constraints and intensifying environmental pollution worldwide, environmental education has acted as a crucial vehicle for fostering ecological and environmental awareness in younger generations. the initial goals of environmental education were to foster global public knowledge about environmental issues and increase individuals’ motivation and skills to protect or improve the natural environment (van de wetering et al., 2022). with the changes in the global environmental agenda and societal development, environmental education has become increasingly focused on education for sustainable development, which emphasizes the cultivation of systemic thinking, interdisciplinary inquiry, and practical competences and covers a diverse range of topics including climate change, the circular economy, green technology, civic engagement, and more.